Political Communication in the Determination of Regional Expenditure Budget (APBD) of Ambon City in 2019 - Tuanaya, Wahab; Muhtar, Muhtar; Khairunisa, Atika; Wance, Marno (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2020)
Ambon City was one of the regions experiencing delay in regional expenditure budget (APBD) planning and its determination from 2010-2014. The delay occured due to communication patterns of related institutions that are not well established. This pattern of unattended communication led to debates between the two institutions which had a fatal impact on budgeting in January to March while the deadline for budgeting is no later than December every year. Delay in determining the regional expenditure budget was the focus of this research in which it analyzed political communication patterns in the executive and legislative institutions in carrying out the authority of budget planning in accordance with applicable regulations. The pattern of political communication that occurred in budget planning determines the running of the budget planning process properly, precisely and accountably. Political communication in the discussion of regional expenditure budget of the Ambon City is a process that occurred in planning and budgeting. Budget planning occurred in the executive and legislative bodies was formed by formal communication patterns about the mechanism of budget planning, as well as informal communication patterns for bargaining, negotiating, and lobbying in communicating the interests between the two institutions. Qualitative research method with a case study approach was used to analyze patterns of political communication in the legislative and executive bodies. Data collection techniques were observation, interview, documentation and the use of related materials. The results of the study revealed that the pattern of external communication between the executive and legislative institutions in the process of determining the regional expenditure budget of Ambon City utilized formal and informal communication channels. Furthermore, the work program matching was done through a recess stage which was accommodated in the KUA-PPAS document and set forth in the view of each faction in the Regional House of Representative (DPRD).